2008
DOI: 10.2486/indhealth.46.239
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Hand Injuries Treated at a Tertiary Care Facility in Western Turkey

Abstract: Abstract:The study was designed to investigate characteristics of work-related hand injuries (WRHI) referred to a University hospital emergency department (ED) in an industrialized region as well as to supply data for preventive strategies. All patients with WRHI referred to the University-based ED in the two-year period were investigated. Sociodemographic and injuryrelated clinical information were analyzed. Out of 746 patients who were admitted to the ED due to occupational injuries within the two-year study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
3
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 20 publications
(27 reference statements)
3
31
3
4
Order By: Relevance
“…In comparison the ratio of male subjects is reported as 76% in the US, 69% in the UK, 59% in Denmark and 83% in Turkey. In Netherland and Denmark, hand injuries peak in the age group 10 -14 years, 44% in 10 -19 years in Canada, 35% (under 15 years) in Turkey [5]- [8]. 65% of the victims of industrial injuries in our study were literate (10 years in school and 3 years diploma) in comparison to 41% in the Turkish study [9]- [11].…”
Section: Discussioncontrasting
confidence: 46%
“…In comparison the ratio of male subjects is reported as 76% in the US, 69% in the UK, 59% in Denmark and 83% in Turkey. In Netherland and Denmark, hand injuries peak in the age group 10 -14 years, 44% in 10 -19 years in Canada, 35% (under 15 years) in Turkey [5]- [8]. 65% of the victims of industrial injuries in our study were literate (10 years in school and 3 years diploma) in comparison to 41% in the Turkish study [9]- [11].…”
Section: Discussioncontrasting
confidence: 46%
“…[2,3] More than 2500 admissions due to occupational injuries are recorded in the health facilities annually in Denizli. [4] Severe injuries and multiple casualties generally tend to be transported with state-run ambulance services (112), while other casualties are handled via the facility's own resources. Around one-third of the patients exposed to work-related injuries (WRI) are referred to the University hospital, which has the most advanced technology in the city.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated the most commonly involved digit as the middle finger, followed by the fourth and index fingers, respectively, regardless of the sector. [4,19] This difference between findings may result from the tendency to use the index finger in textile machines, i.e., while feeding the machine with fabric.…”
mentioning
confidence: 99%
“…Yaralanma günleri açısından yapılan değerlendir-mede Serinken ve arkadaşları tekstil işindeki mesleki yaralanmaları ve Türkiye'nin batısındaki üçüncü basamak sağlık merkezinde tedavi edilen mesleki el yaralanmalarını irdeledikleri çalışmalarında; sırasıy-la %22,5 ve %23,3 oranla, Aksan ve arkadaşları ise %16,7 oranla pazartesi gününü en sık yaralanmanın gerçekleştiği gün olarak belirtilmiştir [8][9][10] . Bizim çalış-mamızda bulduğumuz sonuç da diğer çalışmalar ile uyumludur.…”
Section: Tartıșmaunclassified
“…Serinken ve arkadaşları yaptıkları çalışmada, hastaların %41,4'inin metal makine endüstrisinde ve %16,8'inin ise tekstil işinde çalıştıklarını belirtmişlerdir 9 . Bizim ça-lışmamızda en fazla yaralanan ilk üç meslek grubunu oto sanayi işçisi, kaynakçı ve torna tesviye işinde çalı-şanlar oluşturmaktaydı.…”
Section: Tartıșmaunclassified